INTERIOR MOTIFS AND DESIGNS OF THE MALACCA MOSQUE: A Discussion of the Kampung Kling Mosque - Ahmad, Anisah Bahyah; Mujani, Wan Kamal (Universitas Islam Negeri Alauddin Makassar, 2015)
Arriving in Malacca in 15th century, the Chinese and Indian traders carried their culture and custom with them. It has brought profound implications on aspects of the architecture and motif decoration of mosques in Malacca, which belongs to the Sino-eclectic style. This writing focuses on Sino-eclectic mosque like a Kampung Keling mosque which has three roofs and is located in Malacca town. Because of its strategic location and closeness to other worship places, most of the muslim traders who came to Malacca stop by to pray at the mosque. The remains of their activities at this mosque can be recognized through the motifs and visual designs decorating the mosque which show the immense influence of Chinese and Indian, and therefore, the author of this paper decided to study the magnificent heritage. There are plenty of visual symbols and motifs found in the mosque. They comprise elements of flora, fauna, geometry, cosmos and calligraphy, and are highlighted to increase the aesthetic value and uniqueness of the old mosque. This study yielded fact that the use of the motifs and drawings in the mosque is permitted as it does not violate the boundaries of syariah, which makes Islam easily accepted in Malay.